2013
DOI: 10.1002/eji.201242529
|View full text |Cite
|
Sign up to set email alerts
|

The soluble isoform of CTLA‐4 as a regulator of T‐cell responses

Abstract: CTLA-4 is a crucial immune regulator that mediates both negative costimulation signals to T cells, and regulatory T (Treg)-cell extrinsic control of effector responses.Here we present evidence supporting a novel mechanism for this extrinsic suppression, executed by the alternatively spliced soluble CTLA-4 isoform (sCTLA-4). Analyses of human T cells in vitro show that sCTLA-4 secretion can be increased during responses, and has potent inhibitory properties, since isoform-specific blockade of its activity signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 55 publications
4
94
0
Order By: Relevance
“…In breast cancer, a recent study reported that the presence of cytoplasmic CTLA4 dots was associated with short survival [24]. Although the significance of this expression is unclear, studies in mouse models have shown that the soluble form of CTLA4 can exert a regulatory effect on T cells [25]. …”
Section: Characteristics Of the Cytotoxic T Lymphocyte- Associated Anmentioning
confidence: 99%
“…In breast cancer, a recent study reported that the presence of cytoplasmic CTLA4 dots was associated with short survival [24]. Although the significance of this expression is unclear, studies in mouse models have shown that the soluble form of CTLA4 can exert a regulatory effect on T cells [25]. …”
Section: Characteristics Of the Cytotoxic T Lymphocyte- Associated Anmentioning
confidence: 99%
“…Results shown are an average from triplicate injections of a single batch preparation. All samples had a RSD ≤0.01 b Indicates that the SAgA was solubilized in DMSO following acidic peptide cleavage delivery of a multivalent CTLA-4 mimetic peptide (i.e., SAgA PLP:sF2 ) may actually suppress pro-inflammatory immune responses (38,39). Additionally, current immunological models suggest that "overstimulation" of T cells may induce anergy and be a mechanism of both peripheral and central tolerance (40).…”
mentioning
confidence: 99%
“…Neutralization of sCTLA4 using soluble isoform-specific antibodies increased T cell proliferation and cytokine production (12). In fact, sCTLA4 inhibited production of cytokines IFNγ, IL-2, IL-7, IL-13, and IL-17, yet activated the secretion of immunosuppressive cytokines TGFβ and IL-10 (12, 15). Aside from regulating cytokine production, there are a number of scenarios by which sCTLA4 might regulate the melanoma-specific T cell response.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, sCTLA4 has been shown to be an important immune regulator by inhibiting antigen-specific T cell proliferation and cytokine production (12). Therefore, we hypothesized that patients’ serum levels of sCTLA4 may reflect clinical benefit from treatment with the monoclonal antibody to CTLA4, ipilimumab.…”
Section: Introductionmentioning
confidence: 99%